STACKING OF AG LAYERS ON PT(111) - Fauster, Thomas; et al. (Surface Science, 1995)
Ultrathin Ag films grown epitaxially on Pt(111) were studied by photoelectron forward scattering using synchrotron radiation. The complete angular distributions of the Ag 3d electrons at similar to 500 eV kinetic energy were recorded in a cone with 88 degrees opening angle using a two-dimensional display-type analyzer. The images reveal that the second Ag layer grows at room temperature predominantly in a hcp stacking sequence with respect to the pseudomorphic first Ag layer, After annealing to 750 K most of the second layer Ag atoms assume fee sites, Further Ag layers continue to grow in a fee stacking sequence relative to the first two Ag layers. Annealing does not change the stacking of thicker films. Thick fee Ag films can be grown in a twin orientation with respect to the Pt(111) substrate at room temperature or in the substrate orientation if the second Ag layer is annealed.
Keywords: LOW INDEX SINGLE CRYSTAL SURFACES; PHOTOELECTRON DIFFRACTION; PLATINUM; SILVER; SINGLE CRYSTAL EPITAXY; SURFACE STRUCTURE; X-RAY PHOTOELECTRON SPECTROSCOPY